How do Central Banks react to wealth composition and asset prices? - Castro, Vítor (2010)
We assess the response of monetary policy to developments in asset markets in the Euro Area, the US and the UK. We estimate the reaction of monetary policy to wealth composition and asset prices using: (i) a linear framework based on a fully simultaneous system approach in a Bayesian environment; and (ii) a nonlinear specification that relies on a smooth transition regression model. The linear framework suggests that wealth composition is indeed important in the formulation of monetary policy. However, the attempts of central banks to mitigate undesirable fluctuations in say, financial wealth, may disrupt housing wealth. A similar result can be found when we assess the reaction of monetary authority to asset prices, although concerns about "price" effects are smaller. The nonlinear model confirms these findings. However, the concerns over the wealth and its components are stronger once inflation is under control, i.e. below a certain target. Some disruptions between financial and housing wealth effects are still present. They can also be found in reaction to asset prices, despite being less intense.